Comunicação, saberes e sabores: estratégias de sobrevivência e práticas de bem viver na aldeia Cinta Vermelha-Jundiba - Liberato, Rita Simone Barbosa (2018)
This doctoral dissertation focuses on an educational project developed by the Pankararu and Pataxó indigenous peoples of Cinta Vermelha-Jundiba: a village in the Jequitinhonha Valley, Araçuaí, Minas Gerais, Brazil. In 2005, five indigenous families, who had previously resided in the villages of Apukaré and Guarani Farm, decided to purchase 68 hectares of land and start a new village and a new life project. The initial idea was to create a community space based on permaculture and agroecology. Currently, this strategy has incorporated the concept of living well as an integral element of community practices. My qualitative research seeks to gain insights into the efforts of the Cinta Vermelha-Jundiba villagers to reconstruct ancestral knowledge and articulate strategies of dialogue with the national society. Through the methodology of participatory video, I explore the interwoven domains of education, communication and living well. Overall, I seek to give voice to the members of the community, respecting their individual points of view. The data were collected through participant observation, open interviews, consultation of archival documents and images of the village, as well as official and academic publications concerning the environmental epistemologies of the South, culture, communication, education, ethnic boundaries, gender and traditional knowledge. I captured 600 photographs and conducted 120 hours of interviews with key actors of the village, including the village chief, the shaman, the chief of Apukaré, matriarch of the Pankararu people, members of the five families that comprise the central nucleus of the village, two indigenous school teachers, two young women from the village who work in the field of agroecology and permaculture, and the coordinator of the House of Healing and Harmony. In the current context—which is marked by political, social and environmental pressures, human rights violations and a general depreciation of indigenous peoples' knowledge—the analyses reveal that the community is determined to build a unique educational process based on their agrarian calendar, the knowledge of their elders, and influences from the modern world. I have found that among the stages of planting seeds, pest and weather management, food harvesting and preparation, the villagers of the new territory teach and learn from oral narratives, demonstration, observation, imitation, alliances and dreams. From the territory, and all the tensions and dissensions faced, the community elaborated a way of talking about itself, breaking the hegemonic media systems. The community also produces videos in which the leaders claim the land and share their views on environmental impacts, food and nutritional security, sovereignty, education and health. It is crucial that public policies reflect aspects related to the physical and symbolic survival of ethnic groups and their living well. Thus, it is imperative that the formulation of public policies in these fields begin from the systematic and dialogical listening of indigenous peoples and respond directly to issues relevant to the physical and symbolic survival of the 305 ethnic groups scattered throughout Brazil.